Current Treatment and Application of Hyperthermia for Squamous Cell Carcinoma of the Esophagus - TOH, YASUSHI; IGUCHI, TOMOHIRO; OHGA, SAIJI; SUGIMACHI, KEISHI; SAEKI, HIROSHI; KAGAWA, MASAKI; YOSHIDA, DAISUKE; MORITA, MASARU; SUGIYAMA, MASAHIKO; MAEHARA, YOSHIHIKO; OTA, MITSUHIKO; IKEBE, MASAHIKO; et al. (Thermal Medicine, 2017)
Squamous cell carcinoma of the esophagus (ESCC) is a fairly aggressive disease with a poor prognosis. Surgical resection has been the gold standard of treatment for localized ESCC. However, this carcinoma is fairly sensitive to radiation, as well as chemotherapeutic agents such as cisplatin and 5-fluorouracil. Based on clinical trials conducted mainly by the Japan Clinical Oncology Group (JCOG), preoperative chemotherapy is regarded as the standard treatment for resectable ESCC in Japan. We have applied hyperthermia to ESCC mainly as a preoperative treatment associated with chemoradiotherapy since it has been experimentally proven to enhance the anti-tumor effects of chemotherapeutic agents and irradiation. The long-term survival as well as histological effectiveness was reported to be better in patients who received preoperative hyperthermochemoradiotherapy (HCR) than in those who received preoperative chemoradiotherapy (CRT). Definitive CRT is frequently performed even for resectable ESCC, and salvage treatment for either remnant or recurrent diseases remains an important clinical problem. We have applied hyperthermia simultaneously with chemotherapy as a salvage treatment for such patients, and complete response as well as stable disease was achieved in several patients. Hyperthermia is a promising modality as a salvage treatment and has recently been incorporated into regimens including taxanes. Potential enhancement of hyperthermia with certain drugs should be experimentally evaluated, and the clinical application of hyperthermia may be warranted with other newly-developed regimens.